Niche-dependent modular regulation of the stem cell transcriptome separates cell identity and potential - Amelie Raz; Hafidh Hassan; Yukiko M. Yamashita (Proceedings of the National Academy of Sciences, 2026)
Adult stem cells maintain tissue homeostasis, yet are themselves vulnerable to loss. One common mechanism to replace lost stem cells is dedifferentiation, in which progeny revert to stem cell identity. It is a paradox how stem cells and progeny retain the same stem cell potential while exhibiting distinct current identities of self-renewal, differentiation, and dedifferentiation. Here, we show that the Drosophila male germline lineage solves this paradox via two parallel and complementary mechanisms to separate potential and identity. First, differentiating progeny maintain stem cell potency by inheriting perdurant stem cell mRNAs without actively transcribing them. Second, two known niche signals (Bmp and Jak-Stat) activate distinct sets of targets, defining three identities (self-renewal, differentiation, and dedifferentiation) based on the combination of their on/off states. Together, this study reveals how a pool of dedifferentiation-competent progeny is maintained to regenerate stem cells as needed without resulting in stem cell overproduction and resolves the puzzle of why most stem cell systems require multiple independent niche signals.